2019
DOI: 10.1161/jaha.119.013743
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Desmosine and Abdominal Aortic Aneurysm Disease

Abstract: BackgroundIt is recognized that factors beyond aortic size are important in predicting outcome in abdominal aortic aneurysm (AAA) disease. AAA is characterized by the breakdown of elastin within the aortic tunica media, leading to aortic dilatation and rupture. The aim of this study was to investigate the association of plasma desmosine (pDES), an elastin‐specific degradation product, with disease severity and clinical outcome in patients with AAA.Methods and ResultsWe measured pDES and serum biomarker concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…The high-performance liquid chromatography-capillary electrophoresis (HPLC-CE) method used by Annovazzi et al (2004) [ 14 ] is less specific for plasma desmosines than the LC-MS/MS method we used, since it lacks the specificity to differentiate desmosines from other elastin-derived peptides [ 29 ]. Indeed, our plasma levels are more in line with other studies reported in the literature [ 7 , 8 , 10 , 20 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The high-performance liquid chromatography-capillary electrophoresis (HPLC-CE) method used by Annovazzi et al (2004) [ 14 ] is less specific for plasma desmosines than the LC-MS/MS method we used, since it lacks the specificity to differentiate desmosines from other elastin-derived peptides [ 29 ]. Indeed, our plasma levels are more in line with other studies reported in the literature [ 7 , 8 , 10 , 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…This might contribute to the pathogenesis of peripheral arterial disease in PXE. Elastin degradation is a prominent feature in lung diseases, including chronic obstructive pulmonary disease (COPD) [ 6 ], cystic fibrosis [ 7 ], and idiopathic pulmonary fibrosis [ 8 ], but it has also been shown to be associated with increased carotid femoral pulse wave velocity [ 9 ] and abdominal aortic aneurysms [ 10 ]. Elastin degradation and calcification have been shown to interact, and the different processes might amplify each other [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In thoracic aneurysm patients, increased brillin-1 fragments in the circulation are associated with aortic dissection (30). Along those lines, elastin fragments (desmosin) may be used as biomarker, since plasma desmosin showed a strong correlation with aortic diameter and aortic events in abdominal aortic aneurysm patients (31). Elastin fragments could also discriminate thoracic aorta dissection patients (including MFS) from other cardiovascular patients and controls (32).…”
Section: Measuring the Effect Of Resveratrolmentioning
confidence: 99%
“…Association of increased blood levels of elastin fragments (desmosine), transforming growth factor beta (TGF-β), microfibrillar associated protein 4 (MFAP4), or homocysteine with enhanced aorta pathology is described in MFS [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%